Darwin Koenig letter to Nicholas S. Halmi regarding bird sightings, fall 1977 - Koenig, Darwinet al (1977)
Field notes contributed by Darwin Koenig in a letter to Nicholas S. Halmi with observers Joseph P. Schaufenbuel and Jon Stravers. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1977. Epson - sheet feed/flatbed